The Appropriation of Social, Historical, and Political Spaces: Slovenia and the EU: Преземање на општествените, историските и политичките простори: Словенија и ЕУ - Gržinić, Marina; Kleindienst, Staš; Leban, Sebastjan; Janeva, Kalina (Identities: Journal for Politics, Gender and Culture, 2007)
Author(s): Marina Gržinić, Staš Kleindienst and Sebastjan Leban | Марина Гржиниќ, Сташ Клајндинст и Себастијан Лебан Title (English): The Appropriation of Social, Historical, and Political Spaces: Slovenia and the EU Title (Macedonian): Преземање на општествените, историските и политичките простори: Словенија и ЕУ Translated by (English to Macedonian): Kalina Janeva | Калина Јанева Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 6, No. 2-3 (Summer 2007 - Winter 2008) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 237-267 Page Count: 30 Citation (English): Marina Gržinić, Staš Kleindienst and Sebastjan Leban, “The Appropriation of Social, Historical, and Political Spaces: Slovenia and the EU,” Identities: Journal for Politics, Gender and Culture, Vol. 6, No. 2-3 (Summer 2007 - Winter 2008): 237-267. Citation (Macedonian): Марина Гржиниќ, Сташ Клајндинст и Себастијан Лебан, „Преземање на општествените, историските и политичките простори: Словенија и ЕУ“, превод од англиски Калина Јанева, Идентитети: списание за политика, род и култура, т. 6, бр. 2-3 (лето 2007 - зима 2008): 237-267.